No Direction Home: Photogrammetry and the Post-natural World - MacGregor, Gregor (Curtin University, 2023)
No Direction Home: Photogrammetry and the Post-natural World examines the role of optical technologies in constructing a narrative for a post-natural word. Highlighting the role that the photographic image has played in exacerbating the view of the world as something separate from humanity, and the transitioning of the photograph from an objective image of observed reality to one that is an immersive phenomenological experience.